2018
DOI: 10.15171/ehem.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of noise pollution by analyzing the level of sound loudness resulting from central traffic in Shiraz

Abstract: Background: Today, the effects of environmental pollution on human life and human needs, which reduces the level of community health caused by traffic noise in large cities, are clearly visible by creating irritation and pathogenic conditions. The aim of this study was to assess the risk of noise pollution resulted from central traffic in Shiraz by analyzing its indicators and related components. Methods: By specifying the high traffic jam in Shiraz, the sound and its frequency in 156 points of the city were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In this regard, sound pressure level measuring and frequency analysis were carried out and frequency was below 50 Hz with 115 dB. These two frequencies were determined as the disturbance frequency and the prevailing sound pressure level [59].…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, sound pressure level measuring and frequency analysis were carried out and frequency was below 50 Hz with 115 dB. These two frequencies were determined as the disturbance frequency and the prevailing sound pressure level [59].…”
Section: Methodsmentioning
confidence: 99%
“…This correlation is linear without a threshold. Negahdari et al (2018) examined the danger of noise pollution caused by central traffic in Shiraz and found that the sound pressure levels above the Iranian environmental regulations and the values of the pressure levels were higher than the international limits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are two filters named A and C in this sound meter. The network "A" modifies the frequency response in order to follow approximately the equal loudness curve of 40 phons, while the network "C" modifies approximately the equal loudness of 100 phons [1]. The facepiece filtering respirators have been widely used to reduce human exposure to the aerosol particles.…”
Section: Introductionmentioning
confidence: 99%